Nanomaterials in tissue engineering : fabrication and applications - Gaharwar, A. K. (Woodhead Publishing, 2013)
Nanomaterial technologies can be used to fabricate high-performance biomaterials with tailored physical, chemical, and biological properties. They are therefore an area of interest for emerging biomedical technologies such as scaffolding, tissue regeneration, and controlled drug delivery. Nanomaterials in tissue engineering explores the fabrication of a variety of nanomaterials and the use of these materials across a range of tissue engineering applications. Part one focuses on the fabrication of nanomaterials for tissue engineering applications and includes chapters on engineering nanoporous biomaterials, layer-by-layer self-assembly techniques for nanostructured devices, and the synthesis of carbon based nanomaterials. Part two goes on to highlight the application of nanomaterials in soft tissue engineering and includes chapters on cardiac, neural, and cartilage tissue engineering. Finally, the use of nanomaterials in hard tissue engineering applications, including bone, dental and craniofacial tissue engineering is discussed in part three. Nanomaterials in tissue engineering is a standard reference for researchers and tissue engineers with an interest in nanomaterials, laboratories investigating biomaterials, and academics interested in materials science, chemical engineering, biomedical engineering and biological sciences. Explores the fabrication of a variety of nanomaterials and their use across a range of tissue engineering applicationsExamines engineering nanoporous biomaterials, layer-by-layer self-assembly techniques for nanostructured devices, and the synthesis of carbon based nanomaterialsHighlights the application of nanomaterials in soft tissue engineering and includes chapters on cardiac, neural, and cartilage tissue engineering.
Keywords: Nanostructured materials -- Therapeutic use.; Nanomedicine.; Tissue engineering.; elektronické knihy; electronic books